Roles of Hydrogen Sulfide Donors in Common Kidney Diseases - Ngowi, Ebenezeri Erasto; Sarfraz, Muhammad; Afzal, Attia; Khan, Nazeer Hussain; Khattak, Saadullah; Zhang, Xin; Li, Tao; Duan, Shao-Feng; Ji, Xin-Ying; Wu, Dong-Dong (Frontiers in Pharmacology, 2020)
Hydrogen sulfide (H2S) plays a key role in the regulation of physiological processes in mammals. The decline in H2S level has been reported in numerous renal disorders. In animal models of renal disorders, treatment with H2S donors could restore H2S levels and improve renal functions. H2S donors suppress renal dysfunction by regulating autophagy, apoptosis, oxidative stress, and inflammation through multiple signaling pathways, such as TRL4/NLRP3, AMPK/mTOR, TGF-β1/Smad3, ERK1/2, MAPK, and NF-кB. In this review, we summarize recent developments in the effects of H2S donors on the treatment of common renal diseases, including acute/chronic kidney disease, renal fibrosis, unilateral ureteral obstruction, glomerulosclerosis, diabetic nephropathy, hyperhomocysteinaemia, drug-induced nephrotoxicity, metal-induced nephrotoxicity and urolithiasis. Novel H2S donors can be designed and applied in the treatment of common renal diseases.